2018
DOI: 10.14295/cs.v9i3.1600
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and sanitary quality of seeds of Dimorphandra gardneriana Tul. treated with essential oils

Abstract: Dimorphandra gardneriana, popularly known as fava d’anta, is a medicinal species whose fruits and seeds are used in the manufacture of medicines. The objective of this study was to evaluate the efficiency of clove (Syzygium aromaticum (L.) Merr. & L.M. Perry) and copaíba (Copaifera sp.) essential oils in antifungal treatment of seeds of D. gardneriana and their influence on physiological quality of the seeds. Two experiments were carried out in a completely randomized design using seeds treated with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…For the successful production of seedlings and plant establishment, it is essential to use high quality seeds, expressed by genetic, physical and physiological attributes that are responsible for originating plants with high vigour [10]. One of the factors that can affect the quality of the seedlings is the difficulty of obtaining pathogen-free seeds, once those are one of the main sources of the dissemination and transmission of several pathogens associated with diseases that directly impact plant establishment [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the successful production of seedlings and plant establishment, it is essential to use high quality seeds, expressed by genetic, physical and physiological attributes that are responsible for originating plants with high vigour [10]. One of the factors that can affect the quality of the seedlings is the difficulty of obtaining pathogen-free seeds, once those are one of the main sources of the dissemination and transmission of several pathogens associated with diseases that directly impact plant establishment [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Seed-associated pathogens can cause different forms of harm, such as the loss of germinative power and a reduction in the vigour of the seedlings, including the possibility of pre-emergence and post-emergence death, root rot and infection of the sprout [11]. Studies carried out with Moringa oleifera found several fungal species to be seed transmitted, such as Aspergillus niger, Aspergillus flavus, Alternaria sp, Fusarium sp, Penicillium sp and Phomopis sp.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations